دور الأمواج فوق الصوتية في تشخيص اليرقان - العباس, باسل; زيزفون, حسان; إبراهيم, غدير (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في العام الدراسي 2005-2006 م، وقد شملت /127/ مريضاً مصاباً باليرقان، وكان الهدف من الدراسة إبراز دور الأمواج فوق الصوتية في تشخيص اليرقان كونها وسيلة آمنة وغير راضة وسهلة الإجراء وذات تكلفة اقتصادية مقبولة. تم تصوير المرضى بالأمواج فوق الصوتية واعتماداً على معطيات هذا التصوير تم تقسيم المرضى حسب إمكانية مشاهدة التوسع في الطرق الصفراوية، ثم حاولنا تحديد مستوى الانسداد وتحديد طبيعة الآفة المسببة ثم استكمال دراسة البطن صدوياً لتحديد المرافقات المرضية. وبعد الدراسة الإحصائية ومناقشة النتائج تبين أن للأمواج فوق الصوتية دوراً أساسياً في تفريق اليرقان الانسدادي عن اليرقان غير الانسدادي وفي تحديد مستوى الانسداد، وفي تحديد طبيعة الآفة المسببة لليرقان الانسدادي. وتبين ظهور معطيات صدوية مهمّة في مرضى اليرقان غير الانسدادي بنسبة جيدة من المرضى ولكنها لا تعطي تشخيصاً أكيداً للآفة المسببة لليرقان. The study took place at Al-Assad University Hospital in Lattakia during the academic year 2005-2006. The study included /127/ jaundiced patients. The aim of study was to show the role of ultrasound imaging in jaundice diagnosis, since it is safe, non-traumatic, can be done easily, and inexpensive. So, we did an ultrasound imaging for all patients, then we divided them according to the dilation of the bile ducts. We also tried to determine the level of dilation and to determine the primary lesion. We then continued studying other abdominal organs. We found that ultrasound imaging has an essential role in differentiating between obstructive and non-obstructive jaundice, and in determining the level of dilation as well as in knowing the nature of the lesion which caused the obstructive jaundice. We also found important echoic features in non-obstructive jaundice patients, but these features are not confirmative ones.